2004
DOI: 10.1111/j.1460-2466.2004.tb02616.x
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Lay Models of Uncertainty About Genes' Role in Illness Causation to Guide Communication About Human Genetics

Abstract: Advances in clinical genetics and biotechnology increase the ability to identify individual genetic makeup through genetic services and testing. As a result, genes have become the focus of an increasing number of health messages associated with medical interaction and public communication. This research explored public perceptions (N = 858) of the role of genes in health using problematic integration (PI) theory as a framework. A Genetic Relativism Instrument (GRI) associated with macroframeworks about illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Hence, here we could establish a possible link between religious beliefs, genetic deterministic beliefs, and knowledge in genetics. These results support the importance of religiosity for the formation of genetic deterministic beliefs, as suggested by Parrott et al (2004). The sample of this group was very small, including only 37 participants, making it more difficult to find statistically significant effects.…”
Section: The Effect Of Social Background Factors On Belief In Geneticsupporting
confidence: 55%
See 3 more Smart Citations
“…Hence, here we could establish a possible link between religious beliefs, genetic deterministic beliefs, and knowledge in genetics. These results support the importance of religiosity for the formation of genetic deterministic beliefs, as suggested by Parrott et al (2004). The sample of this group was very small, including only 37 participants, making it more difficult to find statistically significant effects.…”
Section: The Effect Of Social Background Factors On Belief In Geneticsupporting
confidence: 55%
“…Religiosity is of interest in this study since effects from this factor have been shown to influence peoples' beliefs regarding individual traits. Parrott et al (2004) found that some people believe God plays an important role in how genes are expressed and impact health. This is consistent, as we argued previously, with fatalistic thinking in a number of religions (Young et al 2011).…”
Section: Social Explanations For Genetic Determinismmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcripts were not corrected for grammar or for formality in order to capture the oral nature of the discussion. Specific questions asked by the moderators have been reported on elsewhere (see, for example, Condit et al, 2002bCondit et al, , 2003Dorgan et al, 2003;Parrott et al, 2003Parrott et al, , 2004Bates et al, 2003;Bevan et al, 2003). In this study, I took a more global view of the data.…”
Section: Participants and Proceduresmentioning
confidence: 99%